2012
DOI: 10.1128/aem.01536-12
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bowel Microbiota Induced by Feeding Weanlings Resistant Starch Stimulate Transcriptomic and Physiological Responses

Abstract: ABSTRACTThe ability to predictably engineer the composition of bowel microbial communities (microbiota) using dietary components is important because of the reported associations of altered microbiota composition with medical conditions. In a synecological study, weanling conventional Sprague-Dawley rats (21 days old) were fed a basal diet (BD) or a diet supplemented with resistant starch (RS) at 5%, 2.5%, or 1.25% for 28 days. Pyrosequencing of 16S rRNA genes and temporal temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…In general, Lactobacillus and Bifidobacterium are recognised as adept carbohydrate utilising bacteria2122, with genomes containing a high number genes encoding a wide range of carbohydrate transport and utilisation functions212324, so their enrichment in the community of kittens fed the kibbled diets is consistent with complex carbohydrate diet studies in other mammalian species25262728. In contrast, kittens fed the canned diet post-weaning had higher relative abundances of bacteria from the Fusobacterium , Bacteroides and Clostridium genera (Table 2), all of which include representatives that have proteolytic activity293031.…”
Section: Resultsmentioning
confidence: 60%
“…In general, Lactobacillus and Bifidobacterium are recognised as adept carbohydrate utilising bacteria2122, with genomes containing a high number genes encoding a wide range of carbohydrate transport and utilisation functions212324, so their enrichment in the community of kittens fed the kibbled diets is consistent with complex carbohydrate diet studies in other mammalian species25262728. In contrast, kittens fed the canned diet post-weaning had higher relative abundances of bacteria from the Fusobacterium , Bacteroides and Clostridium genera (Table 2), all of which include representatives that have proteolytic activity293031.…”
Section: Resultsmentioning
confidence: 60%
“…Currently, most studies focus on the colonic and fecal microbiota (46,47,50), whereas research on the effect of RS on cecal microbiota is limited. This study is the first to our knowledge to use comprehensive microarray-based profiling to detect the RS effect on cecal microbiota in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…When the energy load was reduced to either normal or low levels, the microbiota population was altered and this reduced the overall metabolic activity in the cultures. Young et al [97] suggested that the temporal changes in microbiota and their metabolism resulting from progressive modifications to substrate availability in weanlings also produces shifts in host transcriptional profiles in an attempt to maintain homeostasis.…”
Section: Early Life Exposures and Intestinal Microbiotamentioning
confidence: 99%